Mathematical modeling of biowall reactors for in-situ groundwater treatment - Donna J. Cedio-Fengya; John G. Stevens (Mathematical Biosciences and Engineering)
In this paper we develop a comprehensive model for the remediationof contaminated groundwater in a passive, in-ground reactor, generallyknown as a biowall. The model is based on our understanding of the componenttransport and biokinetic processes that occur as water passes through abed of inert particles on which a biofilm containing active microbial degraders,typically aerobic bacteria, is developing. We give a detailed derivation of themodel based on accepted engineering formulations that account for the masstransport of the contaminant (substrate) to the surface of the biofilm, itsdiffusion into the biofilm to the proximity of a microbe, and its subsequentdestruction within that degrader. The model has been solved numerically andincorporated in a robust computer code. Based on representative input values,the results of varying key parameters in the model are presented. The relationbetween biofilm growth and biowall performance is explored, revealing that theamount of biomass and its distribution within the biowall are key parametersaffecting contaminant removal.